2020
DOI: 10.1186/s13756-020-00770-1
|View full text |Cite
|
Sign up to set email alerts
|

Enterococcus faecium: from microbiological insights to practical recommendations for infection control and diagnostics

Abstract: Early in its evolution, Enterococcus faecium acquired traits that allowed it to become a successful nosocomial pathogen. E. faecium inherent tenacity to build resistance to antibiotics and environmental stressors that allows the species to thrive in hospital environments. The continual wide use of antibiotics in medicine has been an important driver in the evolution of E. faecium becoming a highly proficient hospital pathogen. For successful prevention and reduction of nosocomial infections with vancomycin res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
90
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(96 citation statements)
references
References 134 publications
(172 reference statements)
4
90
1
1
Order By: Relevance
“…Consistent with this theoretical interpretation of connectivity, we found that its influence was strongest in the hospital-endemic pathogens P. aeruginosa and E. faecium ( Blanc et al, 2007 ; Wurster et al, 2016 ; Zhou et al, 2020 ). Intriguingly, MRSA incidence was not predicted by connectivity.…”
Section: Discussionsupporting
confidence: 85%
“…Consistent with this theoretical interpretation of connectivity, we found that its influence was strongest in the hospital-endemic pathogens P. aeruginosa and E. faecium ( Blanc et al, 2007 ; Wurster et al, 2016 ; Zhou et al, 2020 ). Intriguingly, MRSA incidence was not predicted by connectivity.…”
Section: Discussionsupporting
confidence: 85%
“…A 40% hit rate for activity against S. aureus (6 isolates—DSD004 T , DSD006 T , DSD011 T , DSD015 T , DSD016 T , and DSD037 T ) and A. baumannii (6 isolates–DSD006 T , DSD011 T , DSD037 T , DSD041 T , DSD042 T , and DSD43 T ) ( Table 1 ) were observed. The least hit rate of 13% (2 isolates—DSD006 T and DSD036 T ) was observed against vancomycin-resistant E. faecium , a leading cause of hospital acquired infection [ 79 ]. Only four Streptomyces isolates, i.e., DSD006 T , DSD011 T , DSD041 T , and DSD042 T , were active against the Gram-negative members of ESKAPE pathogens, namely, K. pneumoniae, A. baumannii , P. aeruginosa , and E. cloacae .…”
Section: Resultsmentioning
confidence: 99%
“…However, Temmerman et al (2003a) declared than none of E. faecium strains isolated in their study as contaminant was resistant to vancomycin. Due to their marked antibiotic resistance and ability to cause urinary tract and wound infections, endocarditis, and bacteremia, E. faecium and E. faecalis are well known as important nosocomial pathogens ( Madsen et al, 2017 ; Gao et al, 2018 ; Ben BraĂŻek and Smaoui, 2019 ; Zhou et al, 2020 ). Differently, E. hirae is generally considered a zoonotic pathogen and is rarely isolated from clinical samples derived from humans.…”
Section: Discussionmentioning
confidence: 99%